Research on sensorless and advanced angle control strategies for doubly salient electro‐magnetic motor. Issue 5 (1st May 2016) - Zhou, Xingwei; Zhou, Bo; Guo, Honghao; Wei, Jiadan
Abstract : This paper proposes a sensorless method for doubly salient electro‐magnetic motor (DSEM). The commutation signals are obtained through the comparison between the voltage of silent phase and a pre‐set threshold value based on the characteristic that the excitation back electromotive force (EBEMF) at commutation points is unaffected by the saturation of excitation field. Furthermore, in order to improve the torque output performance of DSEM, a novel sensorless advanced angle control (AAC) is investigated. Unlike traditional AAC, through piecewise linear fitting EBEMF in advance commutation interval, this method does not require the detection of standard commutation points. The experiments implemented on a 12/8‐pole DSEM validate the proposed methods over a wide range of speed and load conditions in both steady and dynamic procedures.